An insight into Russian history from the Middle Ages to the present: Tamás Krausz,Klára Radnóti and Endre Sashalmi (eds.): Apologia Historiographiae: Az orosz történelem évszázadai[Apologia Historiographiae: Centuries of Russian history]. Budapest, Martin Opitz Kiadó, 2023. Pp. 557. ISBN: 978-615-6388-37-7 - Kádár, Anna Katalin (Slavica, 2024)
The collection of studies presented in the volume is a scholarly and informative compilation celebrating the birthday of Professor Gyula Szvák. It publishes new research results by Hungarian scholars into the historical past of the Central and Eastern European Slavic peoples and Russians. The volume is thematically rich, with short studies on the medieval Mongol rule, the political ambitions of the Russian Empire, the Soviet Union, and many other topics. The value of the book lies in the fact that the editors have made it possible – with a view to completeness – to present analyses by outstanding Hungarian representatives of the discipline of Russian Studies.